Integration of Religion and Science in Islamic Education: Holistic-Integralistic Model - Adyatama, Muhammad Fajar (Abjad Journal of Humanities & Education, 2025)
In a learning process, quality is an absolute goal that must be achieved. Therefore, in the development of many models offered by several education experts, one of them is the integration of science and religion in the learning process with holistic-integralistic model. Islamic religious education learning must be able to change something that is still cognitive into something meaningful and valueable that must be internalized in students. Science and religion in the perspective of Islam have the same metaphysical basis, with the aim of revealed and attempted knowledge is to reveal the verses of God, the motivation behind the search for mathematical experience in an effort to know the verses of God in the universe. In the integration of Islamic religious education with science and technology, it is expected that the learning process conducted will be more meaningful and easily understood, so that the purpose of Islamic education in directing students to know, to understand, to appreciate, to believe, to be pious and noble in practicing the teachings of Islam from its main source, the holy book Al-Quran and Al-Hadith, through activities of teaching guidance, training, and the use of experience can be accomplished.